When the “remnants” sing in Kirundi: Herethics in the translation of American culture - Simon Ntamwana; Ratna Nur Fatimah Irakusuma (Universitas Sanata Dharma, 2026)
The article studies the translation of American culture in Seventh-day Adventist (SDA) hymnody in Burundi. It aims at (1) identifying the culture-specific references, language-specific forms, and translation techniques and (2) examining translation shifts with regard to American culture. It used a descriptive qualitative method. Kristeva’s theory of split identity and notion of herethics were combined with Nida’s cultural translation typology. The primary data were obtained from English and Kirundi SDA hymns. 12 hymns purposively selected from The Seventh-day Adventist Hymnal and Christ in Song. The secondary data were collected from books pertinent to American culture, cultural translation, and Seventh-day Adventism. It was discovered that many source culture-bound references are rejected (52.5%) in the Kirundi construction of the domestic Adventist representation of American culture. Similarly, expressions reflecting source-language-specific norms are adapted (90%) to target pragmatics. Apart from a minimal domestication of source culture elements, references to American religious, social, material, ecological, and linguistic culture are manipulated through generalization, specification, deletion, cultural substitution, and adaptation to receptor language norms. The resulting herethics is a construction of an Adventist domestic internal subject that is dominated by a subversion of capitalism, individualism, free will, hegemony, inequality, and romanticism.